Random amplified polymorphic DNA (RAPD) profiling of ageratum conyzoides L - Nurhassekeen, Binti Jeman (Universiti Malaysia Sarawak, UNIMAS, 2013)
The project was conducted to generate DNA profile of Ageratum conyzoides L using RAPD-PCR. Ageratum conyzoides L is a plant species which may look similar to another particular herb that makes the identification of the plant species be difficult. By simply looking at the DNA profile of a plant species, the identification and level of variations can be detected. Samples were collected from two different locations in Sarawak, Malaysia, namely Kuching and Kota Samarahan. The genomic DNA was extracted from the young leaves by using SDS extraction method with some modifications. The quantity and purity of the extracted DNA was analyzed using spectrophotometer. The quality was checked by performing agarose gel electrophoresis. Then, the extracted DNA was subjected to RAPD-PCR analysis. Twenty decamer RAPD primers (OP A1-OP A20) were screened but all failed to produce DNA banding patterns. Optimization of annealing temperature for the RAPD-PCR was done to find the suitable temperature for the primer to anneal at the DNA strand. Optimization of number of cycles also was done for 35 and 45 cycles. However, the optimization also gave the negative results which maybe indicated that all primers are not match with DNA sequence of Ageratum conyzoides L.